Пошук ідентичної структури в молекулярних графах хімічних сполук - Остапенко, О. О. (ХНУРЕ, 2020)
This work is devoted to research on the relationship between the structure of a chemical compound and its properties. It scrutinizes the problems of finding identical structures in chemical compounds represented by molecular graphs. The measure of similarity between the two compounds is determined by metric estimates of proximity. It suggests an isomorphic subgraph search model, extended by combining metric estimates and vertex differentiation methods. The model can be used to improve searching of chemical databases.